PENGARUH PERSEPSI JAMINAN PRODUK DAN KUALITAS INFORMASI TERHADAP KEPERCAYAAN KEPADA PERUSAHAAN DAN IMPLIKASINYA TERHADAP MINAT BELI DI E-COMMERCE (Studi di Bukalapak.com) - Iftikhar, Dala Noor; Magnadi, Rizal Hari (Diponegoro Journal of Management, 2017)
This research  was conducted to find out the influence of perceived assurance of product and information  quality on trust  to the company and its implication on buying interest in e-commerce.This research   uses   perceived   assurance   of  product   and  information   quality   as   the independent variables and trust to the company as the intervening variable, and buying interest in e-commerce as the dependent variable. This  study uses quantitative methodology with Structural Equation Method (SEM)  and uses primer  and secondary data, the data analysis by collecting questionnaire respondents. There are 222 respondents in this research.The analysis results of this research showed that the two independent variables are perceived assurance  of  product (0,336)  and  information  quality  (0,365)  has  a  positive  and significant relationship to the intervening variable that is trust to the company. The two independent variables also has a positive and significant relationship to the intervening variable that is buying  interest in e-commerce, which is perceived assurance of product has 0,336 and information quality  has 0,336. Furthermore, trust to the company as an intervening variable (0,316) has a positive and significant relationship to the intervening variable  that is buying interest in e-commerce.